GLOBAL SECURITY CHALLENGES: INFORMATION SECURITY AND ARTIFICIAL INTELLIGENCE - Suhrob Buranov (International Scientific and Current Research Conferences, 2023)
This article discusses non-traditional forms of security, new challenges to global security, in particular information security and artificial intelligence risks.